Evolution of TOR–SnRK dynamics in green plants and its integration with phytohormone signaling networks. (14th March 2019) - Jamsheer K, Muhammed; Jindal, Sunita; Laxmi, Ashverya
Abstract : TOR–SnRK signaling underwent remarkable evolutionary innovations in green plants and is intimately involved in nutrient, hormone, and stress signaling networks. Abstract: The target of rapamycin (TOR)–sucrose non-fermenting 1 (SNF1)-related protein kinase 1 (SnRK1) signaling is an ancient regulatory mechanism that originated in eukaryotes to regulate nutrient-dependent growth. Although the TOR–SnRK1 signaling cascade shows highly conserved functions among eukaryotes, studies in the past two decades have identified many important plant-specific innovations in this pathway. Plants also possess SnRK2 and SnRK3 kinases, which originated from the ancient SnRK1-related kinases and have specialized roles in controlling growth, stress responses and nutrient homeostasis in plants. Recently, an integrative picture has started to emerge in which different SnRKs and TOR kinase are highly interconnected to control nutrient and stress responses of plants. Further, these kinases are intimately involved with phytohormone signaling networks that originated at different stages of plant evolution. In this review, we highlight the evolution and divergence of TOR–SnRK signaling components in plants and their communication with each other as well as phytohormone signaling to fine-tune growth and stress responses in plants.